Asymmetric relay autotuning – Practical features for industrial use. (September 2016) - Berner, Josefin; Hägglund, Tore; Åström, Karl Johan
Abstract: The relay autotuner provides a simple way of finding PID controller parameters. Even though relay autotuning is much investigated in the literature, the practical aspects are not that well-documented. In this paper an asymmetric relay autotuner with features such as a startup procedure and adaptive relay amplitudes is proposed. Parameter choices and handling of noise, disturbances, start in non-steady state and other possible error sources are discussed. The autotuner is implemented and tested on an industrial air handling unit to show its use in practice. The experiments show good results, and prove that the proposed simple autotuner is well-suited for industrial use. But the experiments also enlighten possible error sources and remaining problems. Abstract : Highlights: A simple asymmetric relay autotuner for industrial use is proposed. Successful experiments on an industrial air handling unit were performed. A thorough discussion of practical aspects of the autotuner is made.